A new leptodactylid frog, genus Atelognathus, from Southern Patagonia, Argentina - Cei, José Miguel Alfredo María (1984)
A new species of leptodactylid frog, Atelognathus salai, is described from basaltic lagoons near Lago Buenos Aires on the eastern slopes of the Andes in the Southern Patagonian Provincia de Santa Cruz, Argentina. The type locality lies between the ranges of other species in northern Patagonia and that of A. grandisonae in southern Chile.